Effects of Ionized Water on Certain Egg Quality Traits and the Levels of Proteins and Enzymes in the Blood of the Japanese Quail Coturnix japonica - Ezzat, Hasanain N.; Shihab , Ihsan M.; Hussein, Mohammad A. (International Journal of Poultry Science, 2017)
Objective: This experiment was conducted to study the effects of ionized water on certain egg quality traits and the levels of proteins and enzymes in the blood of the Japanese quail Coturnix japonica . Materials and Methods: One hundred 42-day-old quail were randomly distributed among five treatment groups with four replicates for each group. The following treatments were used: T1 (control): The birds were provided normal water, T2: The birds were provided alkaline water (pH = 8), T3: The birds were provided alkaline water (pH = 9), T4: The birds were provided acidic water (pH = 6) and T5: The birds were provided acidic water (pH = 5). A Complete Randomized Design (CRD) was used to investigate the effects of the studied treatments on different traits. Results: Significant (p